"Almost wholly the work of Mrs. Lang": Nora Lang, Literary Labour, and the Fairy Books. Issue 4 (2nd October 2019) - Day, Andrea
ABSTRACT: This essay uses documentary evidence to reveal Leonora Blanche "Nora" Lang's elision from the history of children's literature: Lang was actually responsible for the popular Fairy Book series (1889–1913) for which her husband Andrew Lang is now so well known. Accordingly, the essay examines the extraordinary commercial cachet of what Michel Foucault would call Andrew Lang's "author function." It considers the connections between the marginalization of Nora Lang's editorial, translational, and creative labour in favour of her husband's anthropological reputation and the academic tradition inaugurated by Jacob and Wilhelm Grimm (1812) that frames "authentic" female storytelling voices with (and thereby subordinates these to) the learned commentary of male editors.